Imperial subjects : race and identity in colonial Latin America - Fisher, Andrew B., 1970-; O'Hara, Matthew D. (Matthew David), 1970- (Latin America otherwise., 2009)
Gathers together some of the most important scholarship on race in colonial Latin America to examine how historical actors contested, appropriated, and transformed publicly-available markers of difference.